An Improved Method for Initial Sizing of Airbreathing Hypersonic Aircraft - Yalin Dai; Yu Wang; Xiaoyu Xu; Xiongqing Yu (Aerospace, 2023)
One essential problem in aircraft conceptual design is initial sizing in which the aircraft primary parameters such as weight, size, and thrust are estimated for given design requirements. The airbreathing hypersonic aircraft is a type of novel aircraft and has significant differences from conventional aircraft in terms of its flight speed and propulsion system. Traditional initial sizing methods are not suitable for this type of novel aircraft. This paper presents an improved initial sizing method for the conceptual design of airbreathing hypersonic aircraft. An illustrative airbreathing hypersonic aircraft is used to describe the detailed procedure of the method. The weight and size of the aircraft are estimated through the simultaneous solution of the weight equation and the volume equation. Constraint analysis is applied to determine the solution space of the thrust-to-weight ratio and the wing loading. A thrust trade is conducted to find the minimum takeoff gross weight of the aircraft. The impacts of technology parameters on the weight, size, and thrust are investigated by sensitivity analyses. The presented method is based on rational derivation. It can be expected that the initial sizing results from the method are reasonable and satisfactory for conceptual design of the airbreathing hypersonic aircraft.